Educational tools for cultural identity and sharing meetings [PowerPoint presentation] - Henry, Charmaine A. (My University, 2013)
Jamaican proverbs, in their seeming obscurity and obvious profundity, can be quite entertaining. However, like African proverbs, their principal role as a potent creative educational tool, which fosters shared meaning and prepares individuals for the 'school of life,' ought not to be under-estimated (Abubakar, 2011; Hudson, 2009). Jamaican proverbs are indigenous and reformative, utilizing colourful Creole metaphors, humour, and pastoral imagery embedded in African/European cultural situations that encourage, empower, correct, guide, and promote imagination (Williams, 2009). This autoethnography examines the extent to which my mother's use of Jamaican proverbs in my upbringing has given me a deeper understanding of myself and my students, and has shaped my classroom experiences as a media and communication educator. My study induces the practice of self-reflexivity in my dual roles as student/child (at home) and educator/'parent' (in the classroom) at a Jamaican undergraduate media and training institute. It bears out many similarities between my experiences and those of my students: we share past and present Caribbean realities in a dynamic context such as Caribbean tertiary education, with strong colonial retention that oftentimes is unfriendly toward new trends such as Creole in Caribbean education (Devonish, 2012)
Paper presented at the Biennial Conference of The University of the West Indies Schools of Education, 23-25 April, 2013, St. Augustine, Trinidad and Tobago
Keywords: Proverbs; Educational strategies; Higher education; Communication; Conference papers; Jamaica